Anti-cariogenic activities of some East African oleo gum resin crude extracts and essential oils - Mohamed, Scnouci B.; Mirghani, Mohamed Elwathig Saeed; Olorunnisola, K. Saheed; Mohamed, Benali A. (UPM, 2016)
Oleo gum resins are plant exudates commonly used in folk medicine for treating several disease conditions. Anti-cariogenic properties of essential oil (E. oil) and crude extracts obtained from Boswellia frereana (B. frereana), Boswellia carterii (B. carterii) and Commiphora myrrha (C. myrrha) were investigated. Methanol and acetone extracts of the three plants inhibited Streptococcus mutans (S. mutans) and Lactobacillus spp. growth. Hexane extracts showed low anti-microbial activity. The average microbial inhibition was 14.6 mm for S. mutans and 13.8 mm for Lactobacillus spp. regardless of solvent type. B. frereana produced 8% E. oil while B. carterii and C. myrrha gave 5% and 6%. B. frereana E. oil inhibited S. mutans and Lactobacillus spp. more than B. carterii and C. myrrha E. oils.